Work and Individual Factors Influencing Stress Among Nurse Anesthetists in West Java, Indonesia - Richa Noprianty; Akmal Fadhlurrohman; Madinatul Munawaroh; Fikri Mourly Wahyudi (Journal of Public Health and Pharmacy, 2025)
Introduction: Anesthesia services have complex and high-risk work characteristics, which can impact work stress in health workers, including nurse anesthetists in the operating room. This research aims to determine the relationship between work and individual characteristics and the incidence of work stress experienced by nurse anesthetists. Methods: The research method used was quantitative research with a cross-sectional approach. The population in this study were nurse anesthetists in the West Java region who were members of the DPD IPAI JABAR, totalling 765 people. The sample was chosen with non-probability sampling using a stratified random sampling technique based on the work area of the nurse anesthetists, totalling 88 people. The research instrument used a questionnaire about individual characteristics, work characteristics, and workload using the Maslach Burnout Inventory (MBI) questionnaire, created as a Google form sent via the DPD IPAI West Java admin. Data analysis uses regression with chi-square. Results: The research results show that the average work stress is 58.15, with a minimum value of 23, a maximum of 87, and a moderate stress category of 81.8%. Work characteristics related to work stress include hospital type (p-value 0.003), length of work per day (p-value 0.016), and patient’s ASA (p-value 0.013). Meanwhile, individual characteristics related to work stress are age (0.002) and year of work (0.000). Conclusion: Differences in working hours, type of hospital, work patterns, length of service, type of hospitals, as well as lack of seminars or education regarding stress management in the workplace, can influence work stress so that there is a need for clear work mapping for the hospital so that the quality of service can be provided optimally.